Chloride threshold value to initiate reinforcement corrosion in simulated concrete pore solutions: The influence of surface finishing and pH - Figueira, R. B. (2017)
The influence of steel surface finishing and pH of simulated concrete pore solutions (SCPS) on the chloride threshold value (CTV) was evaluated. Steel samples were analysed, with four different finishes: as received (T), diamond-polished (D), polished (P500) and pre-oxidized (DH). The studies were performed in SCPS with pH values of 11.6 and 13.5, and of different chloride concentrations. The electrochemical behaviour of the samples was assessed using open circuit potential, potentiodynamic polarization curves and scanning vibrating electrode techniques. The surface of the steel samples was observed by optical microscopy and SEM/EDS. The results showed that the samples were ranked D > DH > P500 > T for the CTV after which pitting corrosion occurs. The highest chloride threshold value was found in D samples.